Biological Network Analysis of Genes Involve in Embryogenesis of Oil Palm using ClueGO - Sudania, Widyartini Made; Achmad Tanjung, Zulfikar; Toruan-Mathius, Nurita; Liwang, Tony (KnE Life Sciences, 2017)
The application of DNA sequencing technologies has a major impact on molecular biology, especially in understanding genes interaction in a certain condition. Due to a large number of genes produced by this high-throughput technology, a proper analysis tool is needed for data interpretation. ClueGO is a bioinformatics tool, an easy to use Cytoscape plug-in that strongly improves biological function interpretation of genes. It analyzes a cluster or comparing two clusters and comprehensively visualizes their group functions. This tool is applied to identify biological networks of genes involved in embryogenesis of oil palm, the most critical phase in oil palm tissue culture process. Two ESTs sequencing data from the GenBank database under accession number EY396120-EY413718 and DW247764-DW248770 were used in this study. Fifty-two and one hundred eight groups of genes were identified using biological process in Gene Ontology setting from the database of EY396120-EY413718 and DW247764-DW248770, respectively. Thirty-one groups of genes were consistently occurred in both ESTs. According to the literature, these genes play an important role in cell formations and developments, stresses and stimulus responses, photosynthesis and metabolic processes that indicate the involvement of these groups of genes in oil palm embryogenesis processes. ClueGO is the appropriate tool to analyze a large data set of genes in a specific condition, such as embryogenesis of oil palm. Keywords: callus embryogenesis; Cytoscape plug-in; DNA sequencing; expressed sequence tag; KEGG pathways